2005
DOI: 10.1007/s10562-005-6500-z
|View full text |Cite
|
Sign up to set email alerts
|

New precursor for the post-synthesis preparation of Fe-ZSM-5 zeolites with low iron content

Abstract: A new method for preparing ZSM-5 catalysts containing highly dispersed iron species is presented. Iron(III) oxalate was used as the iron precursor in an aerobic aqueous exchange process. The presence of different iron species inside the zeolite pores was investigated by IR spectroscopy of adsorbed NO, which revealed an excellent iron dispersion. The results were compared with those obtained on a Fe-ZSM-5 catalysts prepared by iron(II) chloride sublimation and on samples prepared by controlled migration of fram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 57 publications
4
42
3
Order By: Relevance
“…H 2 -TPR shows that at high temperatures (around 540°C) the FeO x species can be reduced and the 1856 cm )1 band is due to such reduced particles. This is further supported by the fact that such IR bands are observed over iron silicalite, which mainly consist of FeO x particles [6,7,29,[33][34][35][36][37][38][39][40][41]45,46]. No correlations are found between group 3, group 4, and group 5 iron nitrosyl bands and, therefore, these are considered as three different iron species.…”
Section: Drift Spectra Of No Adsorptionmentioning
confidence: 94%
See 2 more Smart Citations
“…H 2 -TPR shows that at high temperatures (around 540°C) the FeO x species can be reduced and the 1856 cm )1 band is due to such reduced particles. This is further supported by the fact that such IR bands are observed over iron silicalite, which mainly consist of FeO x particles [6,7,29,[33][34][35][36][37][38][39][40][41]45,46]. No correlations are found between group 3, group 4, and group 5 iron nitrosyl bands and, therefore, these are considered as three different iron species.…”
Section: Drift Spectra Of No Adsorptionmentioning
confidence: 94%
“…NO forms various iron nitrosyls that are sensitive to the iron species coordination or location in the zeolite channels [32,33]. Therefore, the nature of iron species in zeolite can be effectively probed by characterising the NO stretching vibrations by IR [6,7,29,[33][34][35][36][37][38][39][40][41]. NO adsorption studies over auto-reduced Fe-ZSM-5 catalysts are presented in Ref.…”
Section: Drift Spectra Of No Adsorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Nechita et al [18] also prepared Fe-ZSM-5 zeolite with low iron loading through liquid ion-exchange In experiments, the results of catalytic evaluation showed that the catalytic activity enhanced with increasing the iron loading (Fig. 6).…”
Section: Effect Of Different Iron Precursorsmentioning
confidence: 99%
“…The debate about the nature of the catalytically active sites, isolated Fe 2+ ions or dimeric-oligomeric species in extra-framework positions, has resulted in a incredibly high number of publications on the subject [12,13], as recently reviewed [14]. This interest has also leaded to the development of new ways to introduce Fe species in zeolitic frameworks in controlled manner [15,16]. This huge effort in understanding the structure and chemical reactivity of highly dispersed Fe sites has not been applied to natural zeolites up to now.…”
Section: Introductionmentioning
confidence: 99%